Sebaceous carcinoma of the eyelid: a clinicopathological study. Issue 9 (1st September 1998) - Zürcher, Marlis; Hintschich, Christoph R; Garner, Alec; Bunce, Catey; Collin, J Richard O
Abstract : BACKGROUND: Sebaceous carcinoma of the eyelid is rare. The diagnosis might be difficult because of its ability to masquerade as other periocular lesions. Prognosis is still regarded as being poor compared with most other malignant eyelid tumours with a mortality second only to malignant melanoma. The present study retrospectively analyses clinical and histopathological findings and outcome in a series of patients with sebaceous carcinoma of the eyelid in Britain. METHODS: 43 patients with histologically confirmed sebaceous carcinoma treated at Moorfields Eye Hospital between 1976 and 1992 were subjected to retrospective analysis. Clinical data of all patients were reviewed from the charts; all surviving patients except four cases lost for follow up were re-examined. Histological specimens were reviewed in 41 cases. RESULTS: 23 females and 20 males, mean age 63 years (range 37–79), were treated. Primary therapy was surgery in 37 and radiotherapy in six cases. After a median follow up of 40 months (range 1–148) 30 patients were alive without recurrences, four patients had died from the tumour, and one was alive with local recurrence and distant metastases. Four patients had died of non-tumour related causes. Histologically, unfavourable outcome was correlated with poor tumour differentiation and extensive invasion. CONCLUSION: Early diagnosis and consequent surgical therapy of sebaceous carcinoma of the eyelid leads to a better outcome and higher survival rates than generally assumed. Even local recurrences can be treated successfully. However, sebaceous carcinoma remains a threatening disease, which leads to death in 9% and to mutilating exenteration in 23% of our patients.